A escola, a comunidade e o manguezal : caminhos para a conservação a partir da educação ambiental crítica no bairro Jabotiana em Aracaju-SE - Lima, Sílvia Nascimento Gois (2020)
Historical, political, economic and cultural relations between society and nature have significantly led to socio-environmental impacts on various environments, especially the Permanent Preservation Areas (PPAs), where mangroves are among the various ecosystems. Despite their social and environmental relevance, these environmental systems have received direct influence from anthropic action, especially due to disorganized urban expansion. In this sense, this research aimed to analyze the processes triggered by the practice of Critical Environmental Education for conservation of the mangroves in the Jabotiana neighborhood in Aracaju, from the relationship School, Active Pedagogy and Community and was developed with 35 students in the 1st grade of high school, the State College Professor Joaquim Vieira Sobral. To develop the dissertation, the hypothetical-deductive method was used. From the approach point of view, the research is predominantly qualitative and the methodological paths were constructed from interdisciplinary pedagogical strategies: conversation wheels; Brainstorming; hybrid model of Rotation by Stations; pedagogical workshops; field classes with the students; photographic and poetry exposition; Ecological Walk; Radio Feira; meeting between community and school and the construction of the technical educational product based on the results obtained during the execution of the actions in both formal and non-formal teaching spaces. Through Content Analysis, the results revealed that teaching and learning were strengthened through the use of active methodologies and participatory processes with students and the community, which fostered the construction of new knowledge about the socio-environmental importance of mangroves in urban areas. As a way to highlight the knowledge built, the Socioenvironmental Atlas reveals itself as a technical product capable of reaching the school, the mangrove forest and the community with a view to the conservation of the ecosystem and the valorization of its socio-biodiversity. The strong contribution of this Atlas also consists of the ability to be adapted to other formal teaching environments that have ecosystems in the surroundings, with a view to the formation of critical and reflective social subjects, in the search for changes in the environment. Therefore, with the support of these findings, it is possible to deepen the discussion with the Public Power in order to achieve future achievements for the Jabotiana neighborhood.